Study on Effects of Road Conditions on the Lateral Instability of Tractor Semitrailer Vehicle While Turning Maneuver - TA, Tuan Hung; DUONG, Ngoc Khanh; VO, Van Huong (JST: Engineering And Technology For Sustainable Development, 2022)
Instability of vehicle can be defined as an unexpected response maneuver induce disturbance, occurring in the ground plane: the longitudinal, lateral, pitch, yaw and roll direction, or combinations of those. There are many tractor semitrailer vehicle accidents caused by lateral instabilities, which may be classified into two types: rollover and yaw instability. The rollover occurs when the centrifugal forces imposed on the vehicle during a maneuver exceed the rollover threshold of the vehicle. Yaw instability is often occurred of tractor semitrailer vehicle while turning maneuver on the road with low coefficient of friction. The yaw instability is shown of the loss of motion trajectory or jack-knife. In this paper, a dynamic model of tractor semitrailer vehicle is established based on Multi-body System Method analysis and Newton-Euler equations with Burckhardt’s tire model. This model is applied to evaluate the effect of road conditions on lateral instability of the tractor semitrailer vehicle while turning maneuver. These results can serve as the basis for determining the early warning and controlling the lateral instability of tractor semitrailer vehicle by the dynamic model.